TINJAUAN KELENGKAPAN PENGISIAN SERTIFIKAT PENYEBAB KEMATIAN DI RUMAH SAKIT : LITERATURE REVIEW - Fitriani Fitriani; Ervina Rachmawati; Novita Nuraini; Indah Muflihatin (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2022)
The death cause's certificate is used to document the major cause of the death and to identify the mortality circumstance that used to inform about the health policy and to enhance the strategy of the death prevention and recording. The purpose of this study is to investigate the percentage of completeness towards the filling of the cause of death certificate and to know the factor causing the incompleteness towards the filling of the death cause's certificate. This type of study is the literature review with 11 selected journals according to the inclusion criteria. There are four components in the analysis of the completeness towards the filling of the death cause's certificate namely, patient identification, important report, author authentication, and good recording. In the result of the study, the lowest percentage component was found in the important report at 55.96% and the highest percentage component was found in the author's authentication at 93.72%. The most dominant factor in the incompleteness towards the filling of the death cause's certificate is due to the absence of SOP and the excessive number of components in the death cause's certificate. The suggestion for future researchers is they might redesign the death cause’s certificate by attaching the sections or columns as needed.